Short and Medium-term Outcomes of Omphalocele and Gastroschisis: A Survey from a Tertiary Center - Marques, Alexandra Tavares; Estevão-Costa, José; Soares, Henrique; Fragoso, Ana Catarina (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective To characterize and compare the outcomes of omphalocele and gastroschisis from birth to 2 years of follow-up in a recent cohort at a tertiary center.Methods This is a retrospective clinical record review of all patients with gastroschisis and omphalocele admitted to the Neonatal Intensive Care Unit between January 2009 and December 2019.Results There were 38 patients, 13 of whom had omphalocele, and 25 of whom had gastroschisis. Associated anomalies were present in 6 patients (46.2%) with omphalocele and in 10 (41.7%) patients with gastroschisis. Compared with patients with omphalocele, those with gastroschisis had younger mothers (24.7 versus 29.6 years; p = 0.033), were born earlier (36 versus 37 weeks, p = 0.006), had lower birth weight (2365 ± 430.4 versus 2944.2 ± 571.9 g; p = 0.001), and had a longer hospital stay (24 versus 9 days, p = 0.001). The neonatal survival rate was 92.3% for omphalocele and 91.7% for gastroschisis. Thirty-four patients were followed-up over a median of 24 months; 13 patients with gastroschisis (59.1%) and 8 patients with omphalocele (66.7%) had at least one adverse event, mainly umbilical hernia (27.3% vs 41.7%), intestinal obstruction (31.8% vs 8.3%), or additional surgical interventions (27.3% vs 33.3%).Conclusion Despite the high proportion of prematurity, low birth weight, and protracted recovery, gastroschisis and omphalocele (without chromosomal abnormalities) may achieve very high survival rates; on the other hand, complications may develop in the first years of life. Thus, a very positive perspective in terms of survival should be transmitted to future parents, but they should also be informed that substantial morbidity may occur in the medium term.
Keywords: omphalocele; gastroschisis; anomalies; abdominal-wall defect; morbidity